2017
DOI: 10.1155/2017/9437452
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous Extracorporeal Membrane Oxygenation as a Treatment for Obesity Hypoventilation Syndrome

Abstract: The mortality rate for respiratory failure resulting from obesity hypoventilation syndrome is high if it requires ventilator management. We describe a case of severe acute respiratory failure resulting from obesity hypoventilation syndrome (BMI, 60.2 kg/m2) successfully treated with venovenous extracorporeal membrane oxygenation (VV-ECMO). During ECMO management, a mucus plug was removed by bronchoscopy daily and 18 L of water was removed using diuretics, resulting in weight loss of 24 kg. The patient was wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It is intended to be an alternative to intubation and mechanical ventilation. Venovenous ECMO as an alternative to intubation, as described in several studies and case reports, has demonstrated its potential in similar situations before [1][2][3][4][5][6]. Although venovenous ECMO is known for potential complications, this case demonstrates that the benefits may outweigh the treatment-associated risks in particular populations.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is intended to be an alternative to intubation and mechanical ventilation. Venovenous ECMO as an alternative to intubation, as described in several studies and case reports, has demonstrated its potential in similar situations before [1][2][3][4][5][6]. Although venovenous ECMO is known for potential complications, this case demonstrates that the benefits may outweigh the treatment-associated risks in particular populations.…”
Section: Introductionmentioning
confidence: 68%
“…In this study, the group of most obese patients (six patients with an average BMI of 57.3 kg/m 2 ) had a 100 percent survival rate [5]. A recent case report presented a patient with a BMI of 60.2 kg/m 2 who suffered from obesity hypoventilation syndrome and fluid retention [4]. Because of the high mortality rates for mechanical ventilation in this patient population, the authors applied venovenous ECMO as an alternative to reducing CO 2 by intubation and subsequent mechanical ventilation.…”
Section: Introductionmentioning
confidence: 72%
“…The association between BMI and mortality in VV-ECMO-particularly with respect to ARDS secondary to COVID-19 has yet to be thoroughly explored in the literature. Although few publications prior to the COVID-19 pandemic have demonstrated the feasibility of cannulation, suggested technical modifications to accommodate for increased flow requirements and reported favourable outcomes in obese adult patients placed on VV-ECMO, published results of cohorts with respiratory failure secondary to COVID-19 have predominantly consisted of patients with BMI less than 40 thus limiting awareness of outcomes in this patient population [10,16,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of ECMO utilization in obese patients prior to the COVID-19 pandemic dates back to the early 2000's when case reports described the feasibility of cannulating the morbidly obese and subsequent reports of relatively comparable outcomes [15][16][17][18]. There have also been reports that obese patients on ECMO may have a higher rate of survival compared to non-obese patients; it is unclear if this applies to COVID-19 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Venovenous extracorporeal membrane oxygenation (VV-ECMO) has emerged as a therapeutic modality for the recovery of various refractory acute respiratory failure situations (9). However, few studies have reported the outcomes in patients with OHS and refractory respiratory failure treated with VV-ECMO (10). We sought to report the case of a patient with OHS, complicated with severe PH and acute respiratory failure, who underwent bridging treatment using VV-ECMO.…”
Section: Case Reportmentioning
confidence: 99%